Personalization in B2B Marketing: Leveraging Technology and Customer Insights for Lead Generation - Moosa, Hamza; Koskinen, Henri (2025)
The business-to-business (B2B) marketing industry has experienced a significant transformation as a result of the rise of digital technologies. Digital transformation has led B2B marketing to strategically shift from broad-based strategies to personalized marketing actions. This study investigates how B2B businesses apply new technologies and customer insights to create personalized marketing strategies. In this research, nine B2B marketing professionals from various companies and industries in Finland were interviewed using semi-structured interviews. According to the research, fragmented technology ecosystems and limited insight utilization continue to impede the widespread adoption of personalization as a goal. Companies find it difficult to integrate marketing automation, analytics, and customer relationship management (CRM), which leads to scattered customer insights and manual operations that hinder real-time personalization. It is concluded that B2B marketing personalization is effective when teams from different departments work together, use integrated technology, choose smart strategies, and ensure a good balance between personalization and scale. The research findings can assist marketers, and academics can include them in their discussions about the challenges and opportunities of personalized B2B marketing in companies adopting digital technology.